Relationship between ankle varus moment during gait and radiographic measurements in patients with medial ankle osteoarthritis - Choi, Ji Hye (PLoS One, 2021)
BACKGROUND: Kinetic data obtained during gait can be used to clarify the biomechanical pathogenesis of osteoarthritis of the lower extremity. This study aimed to investigate the difference in ankle varus moment between the varus angulation and medial translation types of medial ankle osteoarthritis, and to identify the radiographic measurements associated with ankle varus moment. METHODS: Twenty-four consecutive patients [mean age 65.8 (SD) 8.0 years; 9 men and 15 women] with medial ankle osteoarthritis were included. Fourteen and 10 patients had the varus angulation (tibiotalar tilt angle≥3 degrees) and medial translation (tibiotalar tilt angle<3 degrees) types, respectively. All patients underwent three-dimensional gait analysis, and the maximum varus moment of the ankle was recorded. Radiographic measurement included tibial plafond inclination, tibiotalar tilt angle, talar dome inclination, and lateral talo-first metatarsal angle. Comparison between the two types of medial ankle osteoarthritis and the relationship between the maximum ankle varus moment and radiographic measurements were analyzed. RESULTS: The mean tibial plafond inclination, tibiotalar tilt angle, talar dome inclination, lateral talo-first metatarsal angle, and maximum ankle varus moment were 6.4 degrees (SD 3.3 degrees), 5.0 degrees (SD 4.6 degrees), 11.4 degrees (SD 5.2 degrees), -6.5 degrees (SD 11.7 degrees), and 0.185 (SD 0.082) Nm/kg, respectively. The varus angulation type showed a greater maximum ankle varus moment than the medial translation type (p = .005). The lateral talo-first metatarsal angle was significantly associated with the maximum ankle varus moment (p = .041) in the multiple regression analysis. CONCLUSION: The varus angulation type of medial ankle osteoarthritis is considered to be more imbalanced biomechanically than the medial displacement type. The lateral talo-first metatarsal angle, being significantly associated with the ankle varus moment, should be considered for correction during motion-preserving surgeries for medial ankle osteoarthritis to restore the biomechanical balance of the ankle.